2019
DOI: 10.3892/etm.2019.7551
|View full text |Cite
|
Sign up to set email alerts
|

miR‑206 regulates alveolar type�II epithelial cell Cx43 expression in sepsis‑induced acute lung injury

Abstract: The present study investigated the relationship between connexin 43 (Cx43) expression in alveolar type II epithelial cells (ATII) and alveolar air-blood barrier permeability, and the effect of microRNA-206 (miR-206) on the expression of Cx43 in sepsis-induced acute lung injury. For the in vivo study, rats were divided into the sham, caecum ligation and perforation (CLP), CLP+Cx43 inhibitors (Cx43-In) and CLP+miR-206 analogs (miR-206-Mi) groups. CLP method was used to prepare an acute lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Sepsis can result in multiple organ failure and is considered a leading cause of mortality in intensive care unit patients ( 21 ). The lung serves as the most susceptible target organ in sepsis that can further develop into life-threating acute respiratory distress syndrome (ARDS), which is the principle risk factor for mortality ( 22 , 23 ). The present study demonstrated that sufentanil protected against sepsis-induced ALI by regulating KNG1-mediated NF-κB and Nrf2/HO-1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis can result in multiple organ failure and is considered a leading cause of mortality in intensive care unit patients ( 21 ). The lung serves as the most susceptible target organ in sepsis that can further develop into life-threating acute respiratory distress syndrome (ARDS), which is the principle risk factor for mortality ( 22 , 23 ). The present study demonstrated that sufentanil protected against sepsis-induced ALI by regulating KNG1-mediated NF-κB and Nrf2/HO-1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Cx43 has been found to be a direct target of miR-206 in many cells, including smooth muscle cells [ 14 ], myocardial cells [ 15 ], type II alveolar epithelial cells [ 15 ] and breast cancer cells [ 16 ]. Cx43 is a gap junction protein that promotes cisplatin cytotoxicity [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many proteins have been reported to be directly targeted by miR-206, including estrogen receptor 1 (ESR1) [ 6 ], MET [ 39 ], NOTCH 3 [ 6 , 39 ], HDAC4 [ 27 ], Gadd45β [ 40 ], and Connexin 43 (Cx43) [ 14 , 15 , 41 ]. Among these targets, Cx43 is a well-defined target molecule of miR-206 in many types of cells, including smooth muscle cells [ 14 ], myocardial cells [ 15 ], type II alveolar epithelial cells [ 15 ] and breast cancer cells [ 16 ]. Cx43 is ubiquitous in cells and is reduced in a variety of tumor cells [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…HE staining of the lower lobes of the right lungs was performed as previously described [ 7 ]. The tissues were observed and photographed under a microscope.…”
Section: Methodsmentioning
confidence: 99%
“…MiRNAs are able to modulate protein expression via binding to 3′-untranslation region (3′-UTR) in the target mRNA [ 5 ]. Some particular miRNAs, such as miR-145 [ 6 ] and miR-206 [ 7 ] have been revealed to be involved in the development of sepsis-induced ALI. miR-125b-5p has been verified to be abnormally expressed in sepsis [ 8 ] and impact of miR-125b on lipopolysaccharide (LPS)-induced ALI has been previously studied [ 9 ], while role of miR-125b-5p in the development of sepsis-induced ALI has not been explored yet.…”
Section: Introductionmentioning
confidence: 99%